A study on the trend of rising fee based income in commercial banking in Singapore - Ho, Chee Sin (2014)
Local and foreign banks in Singapore are riding on a wave of success. In 1993, the Big Four banks registered profit’s growth averaging close to 50%, while Keppel Bank and many foreign banks showed similar spectacular results. The industry players and analysts had commented on how difficult it would be to sustain the recent level of growth and profitability in the years ahead. The important issue for banks now is to understand the nature of their profit to enable them to build on their success.